The internal workplace mechanism : a tool to resolve unfair labour practices within the workplace - Rasivhetshele, A. M.; Mey, M.; Agherdien, N. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
The Labour Relations Act 66 of 1995 (LRA) provides for the legal framework for dispute resolution. The Act encourages employers to resolve labour issues as soon as possible within the workplace, but the internal workplace mechanism does not ensure the elimination of the negative consequences of disputes which may arise. Employers should use the internal grievance procedure to resolve unfair labour practices in a timeous manner within the workplace. However, problems relating to the application of the internal workplace mechanism continue to exist. The purpose of this paper is to indicate the importance of the internal workplace mechanism of an organisation, the grievance procedure, as a tool to use to resolve labour matters relating to unfair labour practices within the workplace. Ultimately, the article offers suggestions for the design and implementation of internal workplace mechanisms that could be effective in the context of unfair labour practices. The paper concludes that the manner in which an organisation applies its internal workplace mechanism can either aggravate or moderate the seriousness of the dispute – and in the case of the former, this may have a negative impact on the level of efficiency in the workplace. Consequently, unfair labour practices result in an aggrieved and unhappy workforce, with employees possibly feeling that an act or omission on the part of their employer may have deprived them of a workplace benefit
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Grievances; Grievance procedure; Internal workplace mechanism; Unfair labour practice; Labor disputes--South Africa